The Use of Live, Frozen and Pottasium Permanganate Treated Moina micrura for Catfish (Clarias macrocephalus) Larvae - Hashim, Roshada; Ali, Ahyaudin (1990)
Live, frozen and pottasium permanganate (KMnO4) treated Moina micrura were fed to catfish (Clarias macrocephalus) larvae for 20 days. The aim of KMnO4 treatment prior to feeding was to minimise the level of microorganisms present in them. micrura culture. The growth rates and feed conversion ratios for the live untreated and KMn04 treated M. micrura were not significantly different. Frozen M. micrura had a significantly lower growth rate and significantly higher feed conversion compared with the live, untreated M. micrura. The results on relative growth and feed conversion of fry fed the treated and untreated suggest that M. micrura retained its nutritive qualities even when treated with 1µM KMn04 and is suitable as a larval feed.